مراقبة مزارع البيوت البلاستيكية والتحكم بها باستخدام شبكات الحساسات والمشغلات اللاسلكية المعتمدة على تقنية ZigBee - خليفة, جمال (Latakia University Journal -Engineering Sciences Series, 2016)
يشكل استخدام شبكات الحساسات اللاسلكية في مراقبة الزراعات المحمية، والتحكم بها، واحداً من المجالات التي لاقت رواجاً واسعاً في الآونة الأخيرة، لما تقدمه هذه الشبكات من خدمات، وتسهيلات، ووثوقية على مستوى المراقبة والتحكم. يسهم هذا البحث في دراسة تطبيق هذه التقنية على البيوت البلاستيكية المنتشرة في بلدنا، وعلى مساحات واسعة. ويقدم حلولاً لعمل شبكات المراقبة والتحكم الخاصة بذلك في الزمن الحقيقي، وبما يضمن أداء جيداً وفقاً لمعايير تقييم أساسة، مثل تخفيض التأخير الزمني، وزيادة في النفاذية ، وزيادة نسبة تسليم الرزم، وتخفيض عدد الرزم المفقودة، مع زيادة حمل الشبكة. وضِع من أجل ذلك عدد من السيناريوهات التي تماثل واقع بناء وتشغيل البيوت البلاستيكية في منطقتنا، اعتماداً على تقنية ZigBee. وقد تم اختبار سيناريوهات عمل شبكات الحساسات اللاسلكية، باستخدام المحاكاة، بما يسمح باستنتاج التوصيات للاسترشاد بها حين العمل على تركيب مثل هذه الشبكات في أماكنها لتعمل بالشكل الأفضل، وذلك من أجل مساحات مختلفة وعدد كبير من الصالات. The use of wireless sensor networks to monitor and control the precise agriculture is one of the areas which received broad concern in recent times, for the services, facilities and the reliability provided by these networks on the monitoring and control level. This research contributes to the study of the application of this technique in greenhouses deployed over large areas in our country. It offers solutions for networks of monitoring and control, in real time, and ensures a good performance according to the essential evaluating criteria, such as reducing the time-delay, and increases throughput, increases the delivery ratio of packets, and reduces the number of packets lost along with increased network load. In order to do that, a number of scenarios are proposed. These scenarios are similar to the reality of the construction and operation of the greenhouses in our region relying on ZigBee technique. Wireless sensors networks of these scenarios have been tested, using simulation in order to make conclusion and recommendations to guide the work while installing such networks in place to work as their best for different areas and a large number of lounges.